Predictors of Complications, Functional Outcome, and Morbidity in a Large Cohort Treated With Flow Diversion. Issue 4 (20th December 2019) - Sweid, Ahmad; Starke, Robert M; Herial, Nabeel; Chalouhi, Nohra; Das, Somnath; Baldassari, Michael P; Alexander, Tyler D; Tjoumakaris, Stavropoula; Gooch, M Reid; Hasan, David; Rosenwasser, Robert H; Romo, Victor; et al.
Abstract: BACKGROUND: A dramatic improvement in obliteration rates of large, wide-necked aneurysms has been observed after the FDA approved the Pipeline Embolization Device (PED) in 2011. OBJECTIVE: To assess the predictors of complications, morbidity, and unfavorable outcomes in a large cohort of patients with aneurysms treated with PED. METHODS: A retrospective chart review of a prospectively maintained database for subjects treated with flow diversion from 2010 to 2019. RESULTS: A total of 598 aneurysms were treated during a period extending from 2010 to 2019 (84.28% females, mean age 55.5 yr, average aneurysm size 8.49 mm). Morbidity occurred at a rate of 5.8% and mortality at a rate of 2.2%. Ischemic stroke occurred at a rate of 3%, delayed aneurysmal rupture (DAR) at 1.2%, and distal intraparenchymal hemorrhage (DIPH) at 1.5%. On multivariate analysis, the predictor of stroke was aneurysm size >15 mm. Predictors of DAR were previous subarachnoid hemorrhage (SAH), increasing aneurysm size, and posterior circulation aneurysm. Predictors of DIPH were using more than 1 PED and baseline P2Y12 value. Predictors of in-stent stenosis were the increasing year of treatment and balloon angioplasty, whereas increasing age and previous treatment were negatively associated with in-stent stenosis. Predictors of morbidity were posterior circulation aneurysms, increasing aneurysm size, and hypertension, and incidental aneurysm diagnosis was protective for morbidity. CONCLUSION: Flow diversion is a safe and effective treatment option for aneurysms. A better understanding of predictive factors of complications, morbidity, and functional outcomes is of high importance for a more accurate risk assessment.